2001
DOI: 10.3923/jbs.2001.235.237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Sowing Dates on the Yield of Tinda Gourd (Citrullus vulgaris) Var. Fistulosus under the Agroclimatic Conditions of D. I. Khan

Abstract: An experiment on Tinda Gourd cv. local was conducted at the experimental area of Faculty of Agriculture, Gomal University, D.I. Khan during 1995 to determine the best date of sowing for obtaining high yield. Experiment comprises six dates of sowing viz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…[13] reported that off-season bottle gourd cultivation leads to higher gross returns, maximum net monetary return due to the higher price of vegetables, and also a higher cost-benefit ratio. Similar results were observed by Khan et al in 2001 [11] in tinda vegetable crops, supporting the opinion given by Aderibigbe and A.T. Benjamin in 2016 [12] .…”
Section: Methodssupporting
confidence: 90%
“…[13] reported that off-season bottle gourd cultivation leads to higher gross returns, maximum net monetary return due to the higher price of vegetables, and also a higher cost-benefit ratio. Similar results were observed by Khan et al in 2001 [11] in tinda vegetable crops, supporting the opinion given by Aderibigbe and A.T. Benjamin in 2016 [12] .…”
Section: Methodssupporting
confidence: 90%
“…Reduction in fruit length due to late season plantation might be due to inhibition of plant growth promoting hormones such as Auxin, Cytokinin, Gibberellin and Ethylene and activation of abscisic acid (ABA) that inhibited the cellular growth of fruit thus resulted reduction in fruit length. Our results are in line with the findings of Khan et al [36]. Similarly, the decreased fruit length in late sowing might be due to the facts that the growth promoters such as auxin, cytokinin, and gibberellin are inhibited and the growth retardant such as ethylene and ABA may got expressed which stop the cell division and cell enlargement resulting in decreased fruit length [37].…”
Section: Figure 2 Various Attributes Of Tomato Influenced By Differesupporting
confidence: 91%
“…Flowering is key factor which influence the fruit set and is mainly dependent on photoperiod and temperature. Khan et al [21] reported that exposure of late sown plants to high temperature interrupt the normal mechanism of plant growth and resulted in early flowering and poor fruit setting Saeed et al [27] that with the extended period of photosynthetic activity, the plants store adequate amount of photosynthates and later use it for production of maximum number of flower buds.…”
Section: Results and Discussion Morphological And Yield Related Traitmentioning
confidence: 99%
“…In general, planting time and field conditions affect plant growth and crop yield. Similarly, planting time of melon has a significant influenceon yield and quality (Saglam and Yazgan 1999;Khan et al, 2001;Refai et al,2008;Dufault et al, 2006). Early sowing of melon varieties significantly affected the flowering and fruit setting due to the effect on the days of germination (Khan et al, 2001).In contrast to the effects of early sowing reported in previous studies, Dufault et al, (2006) indicated no advantage of early planting.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, planting time of melon has a significant influenceon yield and quality (Saglam and Yazgan 1999;Khan et al, 2001;Refai et al,2008;Dufault et al, 2006). Early sowing of melon varieties significantly affected the flowering and fruit setting due to the effect on the days of germination (Khan et al, 2001).In contrast to the effects of early sowing reported in previous studies, Dufault et al, (2006) indicated no advantage of early planting. Therefore, this study aimed to determine the effects of different planting times on yield, quality and nutrient contents different melon genotypes grown in Şırnak, Turkey ecological conditions.…”
Section: Introductionmentioning
confidence: 98%